An experimental investigation and prediction of fatigue crack growth under overload/underload in Q345R steel. (May 2017) - Ding, Zhenyu; Wang, Xiaogui; Gao, Zengliang; Bao, Shiyi
Highlights: Fatigue crack growth tests on Q345R steel are conducted with overload/underload. The retardation effect increases with overload ratio increase and stress ratio decrease. The single underload induces crack growth acceleration. The combination effect of overload/underload is dominated by the overload. A new method is used to predict crack growth for Q345R with variable loading. Abstract: A series of fatigue crack growth experiments on Q345R steel are conducted by a constant amplitude load with a single overload/underload. The fatigue crack growth behavior of Q345R steel with overload/underload is explored in a detailed manner. The retardation effect of the overload with different stress ratio and overload ratio are quantified by retardation length and cycles. The experimental results of Q345R steel show that (1) overload ratio is the key factor that accounts for the retardation effect, (2) overload effect is sensitive to the stress ratio, (3) underload induces the acceleration of the crack growth rate, and (4) overload plays a more dominant role in terms of the effect of the combination of overload and underload. A unified model based on continuum mechanics is used to predict the crack growth rate. The crack growth process is modeled by a new continuous propagation method in considering the loading history. This method successfully predicts the fatigue crack growth rate and lives of specimens under different load conditions. The numerical results are in accordance with that from experimental observations.